2012
DOI: 10.1186/1472-6920-12-114
|View full text |Cite
|
Sign up to set email alerts
|

Measuring students’ approaches to learning in different clinical rotations

Abstract: BackgroundMany studies have explored approaches to learning in medical school, mostly in the classroom setting. In the clinical setting, students face different conditions that may affect their learning. Understanding students’ approaches to learning is important to improve learning in the clinical setting. The aim of this study was to evaluate the Study Process Questionnaire (SPQ) as an instrument for measuring clinical learning in medical education and also to show whether learning approaches vary between ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
3
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 25 publications
4
31
3
6
Order By: Relevance
“…, Emilia et al . ). Two studies used the Approaches to Study Inventory (ASI); also in this case, the versions differed in terms of numbers of items and/or subscales (Stiernborg et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…, Emilia et al . ). Two studies used the Approaches to Study Inventory (ASI); also in this case, the versions differed in terms of numbers of items and/or subscales (Stiernborg et al .…”
Section: Resultsmentioning
confidence: 97%
“…, Emilia et al . ). One study reported Vermunt's Model; this author developed the Inventory of Learning Style (ILS) and qualitatively identified four different modes or styles of learning (Kalaca & Gulpinar ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a broader sense, the study also validates psychometrics in its new application to the measurement of real‐time learning. Previously, the use of psychometrics in medical education has applied to assessment, such as in translating a teacher's subjective observation to objective data as in objective structured clinical examinations, and to learner self‐reporting of ‘soft’ data as in the measurement of learning approaches and motivations . Compared with these applications, the measurement of mental processes implies the presence of trust that subjects have sufficient self‐awareness for accurate self‐reporting.…”
mentioning
confidence: 99%
“…Dada la falta de instrumentos para evaluar estrategias para el aprendizaje clínico, algunos investigadores han adaptado cuestionarios creados para el aprendizaje en salas de clases, como el Study Process Questionnaire, y lo han usado para conocer las aproximaciones de los estudiantes de medicina de Indonesia al aprendizaje clínico 17 . Ésta nos parece una estrategia arriesgada en términos de la validez, dadas las diferencias cualitativas entre el aprendizaje teórico y el experiencial.…”
unclassified